High-temperature quality of accelerated spheroidization on SUP9 leaf spring to enhance machinability. Issue 12 (December 2018) - Chandra, Hendri; Pratiwi, Diah Kusuma; Zahir, Muhammad
Abstract: The high temperature on the austenitization showed the varied results in the fast spheroidization in high carbon leaf spring steel SUP9/55CrMnA. The heating temperature was held for 15 minutes in the austenitization temperature at 800, 850, and 900 °C respectively, which was intended to break cementite lamellar and then proceed to spheroidization at 720 °C for 2 hours. The purpose of this treatment was to enhance machinability, the experiment results showed a significant enhancing in machinability at 800 °C with 180 VHN hardness value and machining performance increased to 78.5% with 54 seconds machining time. The drilling process used an HSS twist drilling 2.5 mm in diameter and a workpiece height of 15 mm under equal spindle speed and load. The machining process is recommended to know the quality of the cementite, which was revealed on the drilling process of the initial specimen, the drill bit was unable to drill the specimen caused by chisel edge blunted. The acceleration spheroidization process under high temperature showed the significant enhancing in machinability of SUP9 leaf spring.